A Tailored Thermosensitive PLGA-PEG-PLGA/Emulsomes Composite for Enhanced Oxcarbazepine Brain Delivery via the Nasal Route - Ghada M. El-Zaafarany; Mahmoud E. Soliman; Samar Mansour; Marco Cespi; Giovanni Filippo Palmieri; Lisbeth Illum; Luca Casettari; Gehanne A. S. Awad (MDPI AG, 2018)
The use of nanocarrier delivery systems for direct nose to brain drug delivery shows promise for achieving increased brain drug levels as compared to simple solution systems. An example of such nanocarriers is emulsomes formed from lipid cores surrounded and stabilised by a corona of phospholipids (PC) and a coating of Tween 80, which combines the properties of both liposomes and emulsions. Oxcarbazepine (OX), an antiepileptic drug, was entrapped in emulsomes and then localized in a poly(lactic acid-co-glycolic acid)-poly(ethylene glycol)-poly(lactic acid-co-glycolic acid) (PLGA-PEG-PLGA) triblock copolymer thermogel. The incorporation of OX emulsomes in thermogels retarded drug release and increased its residence time (MRT) in rats. The OX-emulsome and the OX-emulsome-thermogel formulations showed in vitro sustained drug release of 81.1 and 53.5%, respectively, over a period of 24 h. The pharmacokinetic studies in rats showed transport of OX to the systemic circulation after nasal administration with a higher uptake in the brain tissue in case of OX-emulsomes and highest MRT for OX-emulsomal-thermogels as compared to the IN OX-emulsomes, OX-solution and Trileptal® suspension. Histopathological examination of nasal tissues showed a mild vascular congestion and moderate inflammatory changes around congested vessels compared to saline control, but lower toxic effect than that reported in case of the drug solution.